2022
DOI: 10.1002/biof.1875
|View full text |Cite
|
Sign up to set email alerts
|

Application of peptide biomarkers in life analysis based on liquid chromatography–mass spectrometry technology

Abstract: Biomedicine is developing rapidly in the 21st century. Among them, the qualitative and quantitative analysis of peptide biomarkers is of considerable importance for the diagnosis and therapy of diseases and the quality evaluation of drugs and food. The identification and quantitative analysis of peptides have been going on for decades. Traditionally, immunoassays or biological assays are generally used to quantify peptides in biological matrices. However, the selectivity and sensitivity of these methods cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…Last, in clinical medical research, biomarkers are powerful tools for diagnosing diseases, discovering drugs and monitoring the therapeutic status of patients. 223 Biomarkers can not only identify and assess a patient's tumor-specific cellular immune response, but also predict and monitor a patient's response to immunotherapy. In addition, predictive biomarkers must be developed in parallel with clinical trials to inform which patients and in what order they can be used most effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Last, in clinical medical research, biomarkers are powerful tools for diagnosing diseases, discovering drugs and monitoring the therapeutic status of patients. 223 Biomarkers can not only identify and assess a patient's tumor-specific cellular immune response, but also predict and monitor a patient's response to immunotherapy. In addition, predictive biomarkers must be developed in parallel with clinical trials to inform which patients and in what order they can be used most effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mass of a peptide can be detected by the mass spectrometer, which, in turn, determines the sequence. 14 (The corresponding detection conditions for HPLC: water/acetonitrile = 1/3, run time was 50 min, post run 2 min, and detection wavelength was 210 nm). Peptides with possible antimicrobial effects were selected by comparing the effects on HPLC signals via normal column packing and membrane chromatography packing.…”
Section: Methodsmentioning
confidence: 99%
“…MTT was dissolved using the cell culture solution, and then the 96-well plates with MTT solution were placed in the cell culture incubator for 4 h. 4-Dimethyl sulfoxide was then added to the 96-well plates, and the corresponding absorbance was measured using a multi-well plate reader with a test wavelength of 490 nm. The cell survival proportion can be analyzed according to the absorbance, 14,17 where a high absorbance in the test means a great survival of cells. When the absorbance of the experimental group is close to or higher than the negative control group, it indicates that the experimental group has no toxicity to cells.…”
Section: Methodsmentioning
confidence: 99%
“…The peptidome -consisting of thousands of peptides: remnants of protein degradation; specific precursor-derived peptides such as hormones, cytokines, or growth factors; and translation products of small open reading frames (smORFs) [16] responds dynamically to changes in the body, providing a rich source of potential biomarkers. This results in the rapid expansion of peptidomics research observed in recent years [17,18], demonstrating characteristic peptidomic patterns of many diseases, including various types of cancer [19][20][21]. Furthermore, it has been shown that peptidomic analyses can detect statistically significant differences observed in bottom-up proteomics [22].…”
Section: Introductionmentioning
confidence: 98%